Discovering the Factors Affecting Divorce in Early Marriages: A Systematic Qualitative Study - Hamed Heidari; Seyed Ali Kimiaei; غلامرضا خویی‌نژاد; Ali Mashhadi (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2019)
Aim and Background: Divorce as a social injury has increased in recent years in Iran and worldwide. Researchers have cited a variety of causes, including: severe belief differences, different upbringings, maladaptive personality traits, etc. which lead to conflict and eventually divorce. The purpose of this study was to explore the factors that influence divorce in early marriages.